2003
DOI: 10.1021/bi0346190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Backbone Contacts 3‘ to the Abasic Site on the Cleavage and the Product Binding by Human Apurinic/Apyrimidinic Endonuclease (APE1)

Abstract: The mammalian apurinic/apyrimidinic (AP) endonuclease (APE1) is a multifunctional protein that plays essential roles in DNA repair and gene regulation. We decomposed the APEs into 12 blocks of highly conserved sequence and structure (molegos). This analysis suggested that residues in molegos common to all APEs, but not to the less specific nuclease, DNase I, would dictate enhanced binding to damaged DNA. To test this hypothesis, alanine was substituted for N226 and N229, which form hydrogen bonds to the DNA ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…Stabilization of the kinked abasic substrate is mediated by interactions of one of the APE1 ␣-helixes with the minor groove, and by the insertion grooves to occupy the place of the flipped-out AP site. An extensive site-directed mutagenesis study of APE1 showed that the side chains of Asn-226, Asn-229 and Arg-177, interacting with two downstream AP-DNA phosphates, provide specific binding to abasic DNA [7]. Finally, the abasic sugar moiety is stabilized within the hydrophobic active site pocket, which includes the side chains of Phe-266, Trp-280 and Leu-282.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of the kinked abasic substrate is mediated by interactions of one of the APE1 ␣-helixes with the minor groove, and by the insertion grooves to occupy the place of the flipped-out AP site. An extensive site-directed mutagenesis study of APE1 showed that the side chains of Asn-226, Asn-229 and Arg-177, interacting with two downstream AP-DNA phosphates, provide specific binding to abasic DNA [7]. Finally, the abasic sugar moiety is stabilized within the hydrophobic active site pocket, which includes the side chains of Phe-266, Trp-280 and Leu-282.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing substrate/product binding of molegos common to DNase-1 showed that those distinctive for APES are not directly involved in cleavage, but establish protein-DNA interactions 3' to the abasic site. Site directed mutagenesis showed that one area we found probably contributes to APE'S ability to retain cleaved DNA after removal of the damaged bases [4]. These additional bonds enhance both specific binding to damaged DNA and the processivity of APE1.…”
Section: Identification Of Firnctionnl Iiiotifi III Apelmentioning
confidence: 77%
“…Based on DNA binding assay with product DNA, we concluded that N226 and N229 are important for their product DNA binding. We conclude that the H-bond network at the DNA backbone just downstream of the abasic site is crucial for the product DNA binding, but also affect the substrate DNA binding [4]. **5'-CyS-labeled 26-mer DNA with a single tetrahydrofuran was used.…”
Section: De-fg03-00er63041mentioning
confidence: 98%
See 2 more Smart Citations